Conservative Treatment of Complicated Crown Fracture and Crown-Root Fracture of Young Permanent Incisor-A Case Report with 24-Month Follow-Up - David Marinčák; Vojtěch Doležel; Michal Přibyl; Iva Voborná; Ivo Marek; Jiří Šedý; Radovan Žižka (MDPI AG, 2021)
The complicated crown-root fracture of young permanent teeth is an uncommon traumatic dental injury that is usually treated in a complex way and is demanding not only for the dentist but even for the treated child. In this case report, we present the conservative treatment of a maxillary central incisor in a 10-year-old boy after a traumatic dental injury. Treatment included partial pulpotomy and adhesive fragment reattachment after reflection of the mucoperiosteal flap. The patient was fully asymptomatic at 24-month follow-up, with an aesthetically acceptable outcome. Vital pulp therapy and adhesive fragment reattachment can be a viable treatment option for complicated crown-root fractures, especially when treating immature permanent teeth.